Empirical Linkages among Corporate Governance, Institutional Environment and Economic Growth in Sharia Law Countries - Ssekitoleko, Patrick; Musvoto, Wedzerai (Acta Universitatis Danubius. Œconomica, 2022)
A surfeit of studies endorse both corporate governance and the institutional environment within which firms operate to promote the economic growth of countries, and that both institutions and corporate governance fortify each other. The research investigates the causal relationships among corporate governance, institutional environment and economic growth among Sharia law countries. Country-specific peculiarities and national institutions possess correlative effects on firm-level corporate governance. Thus, it is the study’s imperative to empirically investigate the impact of the Muslim ideology on firm-level corporate governance and institutions in influencing the economic growth of Sharia law countries. Annual data in the period 2006-2018 for a panel of 13 countries was examined using Panel Vector Autoregression and Panel Granger Causality test models. The results indicate that corporate governance has a negative significant effect on economic growth, while economic growth was found to have a positive significant effect on the institutional environment. Unidirectional causality is revealed from corporate governance, institutional environment to economic growth, and from economic growth, corporate governance to institutional environment. Policymakers ought to reshape the extant corporate governance routines and regulations with a view to registering a significant positive effect on economic growth, as corporate governance sets the trend for a reliable and growth-enhancing institutional environment.